The excito –repellency effect of pyrethroid insecticide-treated bednets on An. stephensi under laboratory condition - Hamzeh Ali Pour (Iranian South Medical Journal, 2006)
Background: The excito-repellency effect due to the application of some insecticides is important in interrupting the malaria transmission cycle. The repellency effect of some insecticides also inhibits the entry of mosquitoes into sprayed houses, which in long-term causes alteration in endophilic and exophilic rates. Methods: In this study, a modified excito-repellency (E-R) test box was used. In order to standardize this system, a number of methods and techniques were considered to evaluate the mosquitoes’ reaction to pyrethroid-impregnated nets. A cylindrical guinea – pig holder made up of aluminum mesh was placed within the exposure chamber. Treated and untreated nets covered this holder so that the guinea pig was available to mosquito for bloodfeeding. An exit trap was devised on the rear side of the exposure chamber. Nets were impregnated with lambdacyhalothrin insecticide at the concentrations of 12.5, 25 and 50 mg/m2, deltamethrin at 12.5, 25 and 50 mg/m2 and cyfluthrin at 40, 80 and 100 mg/m2 or unimpregnated in laboratory by standard dipping procedure. The bloodfeeding rate, exit rate, survival rate, mortality rate and recovery rate of mosquitoes were considered. Results: The results obtained using one-way analysis of variance (ANOVA) reflects a significant difference in excito-repellency of tested insecticides (p<0.05). The bloodfeeding rate of exposed mosquitoes to nets treated with lambdacyhalothrin, deltamethrin and cyfluthrin at standard dose of 25 mg/m2 were 15%, 5.3%and 9.3% respectively the exit rates were also 18.2%, 11.2% and 19.7%, and it was 98.9 % in the control group. The survival rate of mosquitoes was 63.2%, 34.9% and 67%, respectively. The bloodfeeding and exit rates for control group were 41.3% and 1.4%, respectively. Conclusion: The excito-repellency evaluation revealed that the deltamethrin-impregnated net was more effective on An. stephensi than lambdacyhalothrin and cyfluthrin insecticides, under laboratory conditions.